Comparative Reactogenicity of Enhanced Influenza Vaccines in Older Adults. (14th May 2020) - Cowling, Benjamin J; Thompson, Mark G; Ng, Tiffany W Y; Fang, Vicky J; Perera, Ranawaka A P M; Leung, Nancy H L; Chen, Yuyun; So, Hau Chi; Ip, Dennis K M; Iuliano, A Danielle
Abstract: Background: We analyzed data from a randomized controlled trial on the reactogenicity of 3 enhanced influenza vaccines compared with standard-dose (SD) inactivated influenza vaccine. Methods: We enrolled community-dwelling older adults in Hong Kong, and we randomly allocated them to receive 2017–2018 northern hemisphere formulations of SD vaccine (FluQuadri; Sanofi Pasteur), MF59-adjuvanted vaccine (FLUAD; Seqirus), high-dose (HD) vaccine (Fluzone High-Dose; Sanofi Pasteur), or recombinant hemagglutinin vaccine (Flublok; Sanofi Pasteur). Local and systemic reactions were evaluated at days 1, 3, 7, and 14 after vaccination. Results: Reported reactions were generally mild and short-lived. Systemic reactions occurred in similar proportions of participants by vaccine. Some local reactions were slightly more frequently reported among recipients of the MF59-adjuvanted and HD vaccines than among SD vaccine recipients. Participants reporting feverishness 1 day after vaccination had mean fold rises in postvaccination hemagglutination inhibition titers that were 1.85-fold higher (95% confidence interval, 1.01–3.38) for A(H1N1) than in those who did not report feverishness. Conclusions: Some acute local reactions were more frequent after vaccination with MF59-adjuvanted and HD influenza vaccines, compared with SD inactivated influenza vaccine, whereas systemic symptoms occurred at similar frequencies in all groups. The association between feverishness and immunogenicity should be further investigated in a larger population. Clinical Trials Registration: NCT03330132. Abstract : In an analysis of data from a randomized controlled trial, we found comparable reactogenicity between MF59-adjuvanted, high-dose, recombinant hemagglutinin, and standard-dose influenza vaccines. An association between feverishness and immunogenicity was also observed but should be further investigated in a larger population.